Entire onion source-derived redox porous carbon electrodes towards efficient quasi-solid-state solar charged hybrid supercapacitor. (20th October 2022) - Shankar, Edugulla Girija; Das, Amit Kumar; Yu, Jae Su
Highlights: Binder-free inherent surface redox onion-derived carbon is used as a positive electrode. NaCl treated onion-derived graphitic carbon is utilized as a negative electrode. Entirely green source-derived quasi solid-state hybrid supercapacitor (QHSC) is fabricated. The solar panel charged QHSC is employed to power a bicycle speedometer. Economical and eco-friendly high-performance supercapacitor is demonstrated. Abstract: Biomass-derived electrodes inherently containing redox-active species have gained extensive attention recently due to their availability, eco-friendliness, sustainability, and low cost. We report novel binder-free faradic surface redox onion-derived carbon positive electrode with nano regime particles by hydrothermal synthesis and Na + and Cl − ions diffused porous carbon negative electrode via a carbonization method. Energy-dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy confirmed the presence of oxidized sulfur and (N-6) pyridinic N-based redox groups inherently present in the as-prepared compounds. The electrochemical analysis of the positive electrode revealed its faradic redox type of energy storage mechanism with an excellent specific capacitance of 1805 F g −1 at the current density of 3 A g −1 as well as appreciable long-term cycling stability (76.8% retention after 10000 charge-discharge cycles). Meanwhile, the negative electrode exhibited a maximum specific capacitance of 373 F g −1 at 1 A g −1 with outstanding long-term cycling stability (100.7% retention after 10000 cycles). The fabricated polyvinyl alcohol-potassium hydroxide gel electrolyte-based quasi-solid-state hybrid supercapacitor (QHSC) delivered excellent energy density and power density of 19.94 Wh kg −1 and 374.99 W kg −1, respectively with an ultralong cyclic life (102.3% retention) over 10000 cycles. Furthermore, the QHSC was connected to a solar panel to store renewable energy. Solar charged QHSC effectively powered a speedometer, enlightening its potential application in advanced sustainable energy storage systems. Graphical Abstract: Image, graphical abstract